THE EVOLUTION OF IMAGERY IN THE WORKS OF WILLIAM SHAKESPEARE - Sevinch Oybek qizi Mirkurbanova; Said-Fozilxon Akmalxonovich Akmalxonov (Лучшие интеллектуальные исследования, 2024)
Abstract:This article conducts a comparative analysis of imagery across different phases of William Shakespeare's literary career, spanning from his early comedies to his later tragedies and romances. By examining the evolution of imagery in select plays, including "A Midsummer Night's Dream," "Macbeth," and "The Tempest," this study seeks to elucidate how Shakespeare's use of imagery evolved over time, reflecting shifts in thematic concerns, stylistic techniques, and dramatic sensibilities. Through close textual analysis and historical contextualization, this article offers insights into the development and sophistication of imagery in Shakespeare's canonical works.